GLADHEN DALAM SENI PERTUNJUKAN TARI TRADISIONAL JAWA - Widyastutieningrum, Sri Rochana (Fakultas Ilmu Budaya Universitas Diponegoro, 2017)
Gladhen in dance performances is always done by its dancers as an effort to be able to show good performance and aesthetic values. Professional dancers are required to create innovation. The birth of professional dancers is strongly influenced by the training process they experienced. To produce a beautiful dance performance, a professional dancer needs hard training and practice, which is called gladhen. This paper discusses on the proccess of training and practice to produce professional Javanese dancers.